Color stability in intracoronal whitening - Fernando José Peña Bengoa; Nicolas Armando Dufey Portilla; Maria Consuelo Magasich Arze; Matias Valenzuela Varas (Editorial Ciencias Médicas, 2020)
Introduction: Intracoronal whitening is a minimally invasive procedure to restore natural color to stained non-vital teeth. The color stability achieved is fundamental to evaluate the predictability of this type of treatment. Objective: Evaluate color stability 3 years after intracameral whitening with carbamide and hydrogen peroxide at various concentrations. Methods: A total 44 premolars were used which had been extracted by orthodontic indication. The premolars were treated endodontically and artificially pigmented with blood chromogenes. The samples were randomly divided into 4 study groups (n = 11): Group A: 37 % carbamide peroxide, Group B: 35 % hydrogen peroxide, Group C: 100 % carbamide peroxide and Group D: control. Four applications were then made of the whitening agent with a 4-days' separation between them. Color was recorded by spectrophotometry, obtaining the values CIE L*a*b* to estimate total color variation between the initial and final parameters of the treatment, as well as control at 3 years. Results: The results were analyzed with Shapiro-Wilk, ANOVA and Mann-Whitney tests, not finding any significant differences in total color variation with respect to the 3 years' control (p > 0.05). Conclusion: The results of the intracoronal whitening studied are stable throughout time, regardless of the type and concentration of the agent used, and any regressive color variation should be attributed to extrinsic factors.